2016
DOI: 10.1016/j.nicl.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Psychological intervention with working memory training increases basal ganglia volume: A VBM study of inpatient treatment for methamphetamine use

Abstract: BackgroundProtracted methamphetamine (MA) use is associated with decreased control over drug craving and altered brain volume in the frontostriatal network. However, the nature of volumetric changes following a course of psychological intervention for MA use is not yet known.Methods66 males (41 MA patients, 25 healthy controls, HC) between the ages of 18–50 were recruited, the MA patients from new admissions to an in-patient drug rehabilitation centre and the HC via public advertisement, both in Cape Town, Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 72 publications
3
80
0
Order By: Relevance
“…CRTs use diverse methods, such as drill and practice exercises, cognitive strategies training, and group discussions (159,162). Consistent with the present review's observations that cognitive deficits overlap in schizophrenia and meth use disorder, preliminary evidence suggests that CRTs are also beneficial in people with meth use disorder (163,164). Especially exciting are the results of two metaanalyses in schizophrenia patients that revealed CRT increased FIGURe 2 | Summary of the neurobiology underlying cognitive impairments in meth use disorder and schizophrenia.…”
Section: Interventions To Improve Cognition In Meth Use Disorder: Inssupporting
confidence: 80%
See 1 more Smart Citation
“…CRTs use diverse methods, such as drill and practice exercises, cognitive strategies training, and group discussions (159,162). Consistent with the present review's observations that cognitive deficits overlap in schizophrenia and meth use disorder, preliminary evidence suggests that CRTs are also beneficial in people with meth use disorder (163,164). Especially exciting are the results of two metaanalyses in schizophrenia patients that revealed CRT increased FIGURe 2 | Summary of the neurobiology underlying cognitive impairments in meth use disorder and schizophrenia.…”
Section: Interventions To Improve Cognition In Meth Use Disorder: Inssupporting
confidence: 80%
“…Consistent with schizophrenia research, a pilot study in people with meth use disorder found improvement in working memory following four weeks of increasingly difficult N-back memory task training, which was also linked to improved impulse control (164). In people with meth use disorder, it is promising that working memory training has been shown to normalize frontostriatal structure and function (163).…”
Section: Targeting Working Memory Deficitsmentioning
confidence: 80%
“…( Asterisk ) Brain scanning data (structural and functional magnetic resonance imaging) was also collected at baseline and follow-up in HC, MUD, TAU and CT groups, and this data is published elsewhere (Brooks et al 2016) with further data currently in preparation…”
Section: Methodsmentioning
confidence: 99%
“…In order to test the effects of WM training, particularly in people with MUD, which can be regarded as the most potent and prevalent drug of abuse in South Africa, associated with the contraction and spread of HIV (Plüddemann and Parry 2012), we have recently developed a smartphone-based WM training intervention in Cape Town, South Africa (Brooks et al 2016), to reach out to the need for a low-cost adjunct to treatment that can target populations whose access to standard treatment is strained but whose access to a smartphone is not (Anthes 2016). Moreover, we have demonstrated that daily patient engagement in our smartphone-based N-back WM task is easy for clinicians to implement as part of their standard treatment programme for SUD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also noted impairments to working memory (Chang et al, 2002;Gonzalez et al, 2007;Rendell et al, 2009). This is interesting, as recent evidence has suggested that cognitive training using the N-back task may be an effective adjunct for treating the symptoms of METH toxicity (Brooks et al, 2016). Unlike spatial or object-memory tasks, working memory is a global process, involving multiple circuits [for review, D'Esposito and Postle (2015)].…”
Section: Molecular Mechanisms and Loci Of Meth Neurotoxicitymentioning
confidence: 99%